2021
DOI: 10.3233/ies-203161
|View full text |Cite
|
Sign up to set email alerts
|

Immediate effects of different types of abdominal exercises on the inter-rectus distance

Abstract: BACKGROUND: The effects of abdominal exercises on the inter-rectus distance are unclear. OBJECTIVE: To compare the inter-rectus distance at rest and during different abdominal exercises: abdominal crunch, abdominal crunch with transversus abdominis pre-activation and hypopressive exercise. METHODS: A transversal experimental study was carried out in 98 healthy adults without diastasis recti abdominis were recruited. Measurements were assessed using ultrasound imaging, and two points were evaluated: just above … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…When absolute values of IRD width were taken into account, some good-quality images yielded an infraumbilical IRD size of 0mm, indicating invisible linea alba at the level halfway between the pubic bone and the lower umbilical margin. In other studies [3], the mean linea alba width in nulliparas was 0.22cm±0.29 (at 4.5cm below the umbilicus) and 0.65±0.23 (at the lower margin of the umbilical ring), or 0.43cm±0.29 (at 2.5cm below the umbilicus). Liaw et al [1] refer to the results of ICCs between 0.85 and 0.95 of their previous study (published in Chinese), where twenty-six healthy nulliparas were measured at four locations.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…When absolute values of IRD width were taken into account, some good-quality images yielded an infraumbilical IRD size of 0mm, indicating invisible linea alba at the level halfway between the pubic bone and the lower umbilical margin. In other studies [3], the mean linea alba width in nulliparas was 0.22cm±0.29 (at 4.5cm below the umbilicus) and 0.65±0.23 (at the lower margin of the umbilical ring), or 0.43cm±0.29 (at 2.5cm below the umbilicus). Liaw et al [1] refer to the results of ICCs between 0.85 and 0.95 of their previous study (published in Chinese), where twenty-six healthy nulliparas were measured at four locations.…”
Section: Discussionmentioning
confidence: 62%
“…In physiotherapy, conventional ultrasound imaging (USI) is commonly used for non-invasive measurement of the inter-recti distance (IRD) [1,2], and pregnancy-related diastasis recti abdominis (DRA) when assessing, for example, the effectiveness of postpartum physical exercises [3,4,5,6]. Desings of these studies usually require IRD measurements with USI in both pregnancy-related DRA subjects and nulliparous controls [7,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…All 49 included publications (published between 2008 and August 2022) were related to physiotherapy or physical exercise/training and described IRD measurements using USI. Eight studies were from Canada [8,17,20,33,48,[53][54][55] and nine from Spain [11,[42][43][44][45][56][57][58][59]. Countries with two studies were Brazil [60,61], the USA [9,62], the UK [16,63], Norway [13,37], New Zealand [47,64], and China [65,66].…”
Section: Characteristics Of Sources Of Evidencementioning
confidence: 99%
“…Among others, it has been used to measure the width of the fibrous linea alba, also called the inter-recti distance (IRD) [6,7]. The most common purpose of this measurement is to investigate pregnancy-related diastasis recti abdominis (DRA) or monitor the impact of specific exercises on this condition [8][9][10][11][12][13]. DRA mostly develops in advanced pregnancy and manifests itself as an overstretched linea alba leading to the excessive separation of the recti abdominis muscles.…”
Section: Introductionmentioning
confidence: 99%
“…The IRD was measured just above the umbilicus (U point) and halfway between the U point and the xiphoid (UX point) during rest and performing the three abdominal exercises. With the obtained results, the authors found that the abdominal crunch with transversus abdominis preactivation influenced a significant increase in IRD when compared to rest in UX point, abdominal crunch, and hypopressive exercise in U point [ 45 ].…”
Section: Treatmentmentioning
confidence: 99%